The Effect of Hyphoteching Method to Increase Students Speaking Ability at The Eleventh Grade students’ of MA YASMI DURI - Dian Lestari; Setiawati; Dini Deswarni (DIMAR: Jurnal Pendidikan Islam, 2020)
The objective of this research was to invest the effect of implementation of hypnoteaching toward eleventh grade to increase students’ speaking ability. The research was facused to know the significant effect of implementation hypnoteaching method at MA YASMI DURI. The population are 42 persons of eleventh grade that consists of two classes and the sample are 16 persons of IPA 1 Class. The research design was pre-experiment with pre-test and post-test design. The are two variables, they are hypnoteaching method and speaking ability, and then to analyze the data obtained,the research used Paired sample T-test. Based on the data analysis and its result, the writer knows that mean score of students in pre – test was 50.5 and mean score of students in post-test  was 67.25 and the result of paired sample T-test was Tvalue = 6,898, by df is 15. Based on the table of Tvalue, for df  15, Ttable significant 5%  is 2,13 and Ttable significant 1% is 2,95. The writer can make a conclusion that implementation of hypnoteaching method toward speaking ability is categorized in “Ha” level based on the experiment classroom, and there is significant effect of implementation of hypnoteaching method toward eleventh grade student  speaking ability at IPA 1 class. the result indicate that there is significant effect difference on implementation hypnoteaching method, where post-test improvement score than the pre-test score